Sport brand coexistence, competition and synergy: case study of the Sparta Prague ice hockey and football clubs - Crossan, W.; Šíma, J.; Kaprálková, M. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
Sparta Prague, one name, one identity, multiple sports, multiple owners, emblematic of the frequent singular nomenclature, yet multifaceted, sports portfolio of European sport. This article examines the coexistence of the ice hockey club HC Sparta Prague and the football club AC Sparta Prague, focusing on management decision making and fan product decision making. While fans negotiate the allocation of their time and resources between the Czech Republic`s most cherished sporting disciplines, football and ice hockey, they do so within the framework of preferred brand loyalties. Meanwhile, marketing executives in both realms strategize whether to pursue synergistic collaborations or engage in competitive endeavours, all while navigating the terrain of entrenched fan allegiances. Despite the historical unity and shared nomenclature, Sparta hockey and Sparta football function as distinct corporate entities. In the Czech market, fans demonstrate steadfast loyalty to their preferred local brand across sports, thereby shaping both substitutive and complementary relationships between the two. Each club endeavours to optimize fan engagement, cultivate sponsor relations, and leverage broadcasting revenue within the confines of a finite, yet segmented market. Through synthesizing insights garnered from interviews with club managers and data derived from fan surveys, this study seeks to demonstrate the elements of substitution and complementarity within the collective brand identity of Sparta Prague.